Screening of COVID-19 in children admitted to the hospital for acute problems: preliminary data - Nicoletti, Angela; Talarico, Valentina; Sabetta, Lucilla; Minchella, Pasquale; Colosimo, Manuela; Fortugno, Carmelo; Galati, Maria Concetta; Raiola, Giuseppe (Acta Biomedica Atenei Parmensis, 2020)
Background: The new Coronavirus identified in Whuan at the end of 2019 (SARS-CoV-2) belongs to the Beta Coronavirus genus and is responsible for the new Coronavirus 2019 pandemia (COVID-19). Infected children may be asymptomatic or present fever, dry cough, fatigue or gastrointestinal symptoms. The CDC recommends that clinicians should decide to test patients based on the presence of signs and symptoms compatible with COVID-19. Material and methods: 42 children (the majority < 5 years of age) were referred, to our Pediatric Department, as possible cases of COVID-19 infection. Blood analysis, chest X-ray, and naso-oropharyngeal swab specimens for viral identification of COVID-19 were requested. Results: None of the screened children resulted positive for COVID-19 infection. At first presentation, the most frequent signs and symptoms were: fever (71.4%), fatigue (35.7%) and cough (30.9%).  An  high  C-reactive protein value and abnormalities of chest  X-ray (bronchial wall thickening) were detected in 26.2% and 19% of patients, respectively. Almost half of patients (45.2%) required hospitalization in our Pediatric Unit and one patient in Intensive Care Unit. Conclusions: Testing people who meet the COVID-19 suspected case definition criteria is essential for clinical management and outbreak control. Children of all ages can get COVID-19, although they appear to be affected less frequently than adults, as reported in our preliminary survey. Further studies are needed to confirm our observations.